Metabolic alterations in a rat model of takotsubo syndrome. Issue 8 (12th March 2021) - Godsman, Nadine; Kohlhaas, Michael; Nickel, Alexander; Cheyne, Lesley; Mingarelli, Marco; Schweiger, Lutz; Hepburn, Claire; Munts, Chantal; Welch, Andy; Delibegovic, Mirela; Van Bilsen, Marc; Maack, Christoph; et al.
Abstract: Aims: Cardiac energetic impairment is a major finding in takotsubo patients. We investigate specific metabolic adaptations to direct future therapies. Methods and results: An isoprenaline-injection female rat model (vs. sham) was studied at Day 3; recovery assessed at Day 7. Substrate uptake, metabolism, inflammation, and remodelling were investigated by 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography, metabolomics, quantitative PCR, and western blot (WB). Isolated cardiomyocytes were patch-clamped during stress protocols for redox states of NAD(P)H/FAD or [Ca 2+ ]c, [Ca 2+ ]m, and sarcomere length. Mitochondrial respiration was assessed by seahorse/Clark electrode (glycolytic and β-oxidation substrates). Cardiac 18 F-FDG metabolic rate was increased in takotsubo ( P  = 0.006), as was the expression of GLUT4-RNA/GLUT1/HK2-RNA and HK activity (all P  < 0.05), with concomitant accumulation of glucose- and fructose-6-phosphates ( P  > 0.0001). Both lactate and pyruvate were lower ( P  < 0.05) despite increases in LDH-RNA and PDH ( P  < 0.05 both). β-Oxidation enzymes CPT1b-RNA and 3-ketoacyl-CoA thiolase were increased ( P  < 0.01) but malonyl-CoA (CPT-1 regulator) was upregulated ( P  = 0.01) with decreased fatty acids and acyl-carnitines levels ( P  = 0.0001–0.02). Krebs cycle intermediates α-ketoglutarate and succinyl-carnitine were reduced ( P  < 0.05) as was cellular ATP reporter dihydroorotate ( P  = 0.003). Mitochondrial Ca 2+ uptake during high workload was impaired on Day 3 ( P  < 0.0001), inducing the oxidation of NAD(P)H and FAD ( P  = 0.03) but resolved by Day 7. There were no differences in mitochondrial respiratory function, sarcomere shortening, or [Ca 2+ ] transients of isolated cardiomyocytes, implying preserved integrity of both mitochondria and cardiomyocyte. Inflammation and remodelling were upregulated—increased CD68-RNA, collagen RNA/protein, and skeletal actin RNA (all P  < 0.05). Conclusion: Dysregulation of glucose and lipid metabolic pathways with decreases in final glycolytic and β-oxidation metabolites and reduced availability of Krebs intermediates characterizes takotsubo myocardium. The energetic deficit accompanies defective Ca 2+ handling, inflammation, and upregulation of remodelling pathways, with the preservation of sarcomeric and mitochondrial integrity. Graphical Abstract: